Embedding Aspen Custom Modeller for Bioethanol Fermentation Into the Aspen Plus Flowsheet Simulator - Nosaibeh Nosrati-Ghods (Chemical Engineering Transactions, 2020)
Commercial processes used to produce first generation biofuels are mature. In this study, a kinetic model using the equation-oriented process modelling tool Aspen Custom Modeller (ACM) was embedded into the process simulation environment of Aspen Plus and used to simulate industrial bioreactors with cell recycle for bioethanol production. To embed a native module in a process simulation environment, the legacy codes written in ACM were treated as a black box and integrated into the component-based framework. The compliance of ACM to Aspen Plus allows for proper integration of the reactor simulator developed for the fermentation process for bioethanol production using kinetic models. The aim of this research is to improve the ability to use custom kinetic models of fermentation processes, developed in equation-oriented modelling tools, within a sequential modular flowsheet simulator. The results obtained showed the accuracy of the selected kinetic model in ACM with less than 1% difference to industrial data, while a stoichiometric model showed approximately 9% difference to the industrial data. The simulation shows that ACM integrated into Aspen Plus allows for complex biological processes to be predicted accurately in terms of biomass growth, ethanol production and sugar consumption.